TRIM21 promotes ubiquitination of SARS‐CoV‐2 nucleocapsid protein to regulate innate immunity. Issue 4 (13th April 2023) - Mao, Shenglan; Cai, Xuefei; Niu, Siqiang; Wei, Jie; Jiang, Ning; Deng, Haijun; Wang, Wen; Zhang, Jing; Shen, Shimei; Ma, Yuanyan; Wu, Xiaoli; Peng, Qiling; et al.
Abstract: The innate immune response is the first line of host defense against viral infections, but its role in immunity against SARS‐CoV‐2 remains unclear. By using immunoprecipitation coupled with mass spectroscopy, we observed that the E3 ubiquitin ligase TRIM21 interacted with the SARS‐CoV‐2 nucleocapsid (N) protein and ubiquitinated it at Lys 375 . Upon determining the topology of the TRIM21‐mediated polyubiquitination chain on N protein, we then found that polyubiquitination led to tagging of the N protein for degradation by the host cell proteasome. Furthermore, TRIM21 also ubiquitinated the N proteins of SARS‐CoV‐2 variants of concern, including Alpha, Beta, Gamma, Delta, and Omicron together with SARS‐CoV and MERS‐CoV variants. Herein, we propose that ubiquitylation and degradation of the SARS‐CoV‐2 N protein inhibited SARS‐CoV‐2 viral particle assembly, by which it probably involved in preventing cytokine storm. Eventually, our study has fully revealed the association between the host innate immune system and SARS‐CoV‐2 N protein, which may aid in developing novel SARS‐CoV‐2 treatment strategies.